Current status of immune checkpoint inhibition in early-stage NSCLC. (29th May 2019) - Vansteenkiste, J; Wauters, E; Reymen, B; Ackermann, C J; Peters, S; De Ruysscher, D
Abstract: Immune checkpoint inhibition (ICI) immunotherapy has revolutionized the approach to metastatic non-small-cell lung cancer (NSCLC). In particular, antibodies blocking the inhibitory immune checkpoints programmed death 1 (PD-1) and its ligand (PD-L1) are associated with higher response rates, improved overall survival and better tolerability as compared with conventional cytotoxic chemotherapy. Recently, ICI has moved from the second-line to the first-line setting for many patients with non-oncogene-addicted NSCLC, either alone or in combination with chemotherapy. The next logical step is to examine this therapy in patients with non-metastatic NSCLC to improve long-term overall survival and cure rates. For patients with unresectable stage III NSCLC, ICI with durvalumab after concurrent chemoradiotherapy has brought a major improvement in 2-year progression-free and overall survival, which holds promise for an improved cure rate. As the relapse pattern in patients with completely resected early-stage NSCLC is predominantly systemic, high expectations rest on the integration of ICI therapy in their treatment approach. A large number of studies with adjuvant or neo-adjuvant ICI are ongoing and will be discussed here. The advent of stereotactic ablative radiotherapy has brought a valid alternative treatment of patients unfit for or not willing to undergo surgery. Data on combining systemic therapy and stereotactic ablative radiotherapy are virtually non-existent, but there is a strong biological rationale to combine radiotherapy and ICI therapy. Early findings in small feasibility studies are promising and now need to be explored in well-designed phase III trials.